71 Introducing the ABCDE: foundation doctor led teaching. (17th November 2016) - Simon, EV; Riley, F; Richards, D; Karbowiak, M; Moonan, A; Mehta, A; Dore, E; Broom, C; Gosling, N; Burnett, J
Abstract : Background/context: A Simulation Society was founded by undergraduates at a London teaching hospital in order to gain exposure to simulation. Junior doctors created a teaching programme for the SimSoc entitled "Undergraduate Simulation and Skills Course". The focus of the teaching was to introduce an ABCDE approach to assessment, to practise clinical skills and to refine non-technical skills, in order to cultivate the skills and attitude required to manage an unwell patient. Methodology: Weekly teaching incorporating medium fidelity simulated scenarios and part-task trainers for clinical skills. Teaching ratios of 2:1 in the simulation and 1:1 on clinical skills (assessed using a competency check list). Content designed to align with the local curriculum. Facilitated simulation sessions of common medical emergencies with participant priming exercises and post-scenario debriefs including student peer review (using a locally designed structured observation tool). Pre/post course questionnaire on confidence with clinical skills, and understanding of the ABCDE approach. Faculty peer review from recognised trained trainers and educational experts from the local simulation team. Outcomes/results: 38 students received teaching from 15 juniors (from FY1 to CT2) over 4 weeks. Undergraduate exposure to protected, practical teaching time. Improved knowledge of the clinical assessment, in order to underpin their undergraduate teaching on diagnosis and management. Opportunity for junior doctors to hone their teaching in a supported environment. Receiving coaching and feedback from an expert educational faculty. Potential impact: The teaching was exceptionally well received by SimSoc. The impact of this new teaching model not only assists undergraduates in their learning and their exposure to a clinical environment, but also empowers Junior Doctors to refine their teaching skills. Future plans include extending this teaching model to other London medical schools, and creating a supportive environment to induct students into technology enhanced learning.